2001
DOI: 10.1159/000046836
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Learning as a Cause and Treatment of Central Dysfunction

Abstract: Conductive hearing loss produced by middle ear disease (MED) is very prevalent in the first 5 years of childhood. Both MED in children and prolonged ear plugging in animals lead to a binaural hearing impairment that persists beyond the duration of the peripheral impairment. However, after cessation of the MED, or removal of the ear plug, binaural hearing gradually improves. We suggest here that this improvement is a passive form of auditory learning. We also show that active auditory learning, through repetiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Since this was an exceptionally long study (27–101 days), we hypothesize that the long-term unilateral mold induced some hearing loss to the blocked ear. This is in line with other findings showing that temporary conductive hearing loss leads to a binaural hearing impairment that lasts beyond the duration of the impairment (for a review, see Moore et al, 2001). No other study implementing long-term monaural blocks obtained such an effect, but no other occluded the ear for such a long period.…”
Section: Adaptation Aftereffectssupporting
confidence: 92%
“…Since this was an exceptionally long study (27–101 days), we hypothesize that the long-term unilateral mold induced some hearing loss to the blocked ear. This is in line with other findings showing that temporary conductive hearing loss leads to a binaural hearing impairment that lasts beyond the duration of the impairment (for a review, see Moore et al, 2001). No other study implementing long-term monaural blocks obtained such an effect, but no other occluded the ear for such a long period.…”
Section: Adaptation Aftereffectssupporting
confidence: 92%
“…Similarly, children who experience a transient hearing loss have difficulty with binaural hearing (Hall et al, 1995; Hall et al, 1998; Hogan et al, 1996; Moore et al, 1991; Pillsbury et al, 1991) and speech processing (Gravel et al, 1992; Gravel et al, 1996; Hall et al, 2003; Jerger et al, 1988) gradually improve once peripheral hearing is restored. Even adult humans with earplug induced or age related hearing loss benefit from training (Ferguson et al, 2014; Irving et al, 2011; Moore et al, 2001). Since training is unlikely to restore cochlear function, the resulting behavioral improvements are likely due to central mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In the first years of life, it is assumed that auditory and language development undergo a sensitive period [Moore, 2002;Moore et al, 2001]. As auditory input during this time has a stronger effect on developing certain skills than prior or after, even a temporally limited deprivation, as occurs during OM incidents, can affect auditory and language abilities.…”
Section: Discussionmentioning
confidence: 99%
“…As auditory input during this time has a stronger effect on developing certain skills than prior or after, even a temporally limited deprivation, as occurs during OM incidents, can affect auditory and language abilities. On investigating the consequences of auditory impairments during this time, Moore et al [1999Moore et al [ , 2001 found a decline of binaural hearing in animals that were unilaterally ear-plugged in juvenile. They also found that, after a period of hearing loss, binaural hearing improves when peripheral function is normal over a time.…”
Section: Discussionmentioning
confidence: 99%